2015
DOI: 10.1002/berj.3193
|View full text |Cite
|
Sign up to set email alerts
|

Teacher shortage and attrition: Why do they leave?

Abstract: This article examines the professional integration of beginning teachers in French-speaking Belgium and the factors predicting an exit from the profession during the first years of their careers. The analysis of four successive cohorts of new teachers indicates that exit rates are very high during the first year but show a gradual decline afterwards. The exit rates are also much higher in secondary education than at pre-school and primary levels. According to the international literature, this research also sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(66 citation statements)
references
References 30 publications
1
55
0
10
Order By: Relevance
“…This could suggest that schools with more socially disadvantaged students are associated with more attrition or turnover, but this is not so clear. Dupriez, Delvaux, and Lothaire (2015), for example, did not find a significant relationship between these two variables, and, although Borman and Dowling (2008) found a significant relationship in their meta-analysis, the effect size was quite small (only a 5% greater possibility of attrition when the majority of students were from a low socioeconomic background). On the other hand, Allen, Burgess, and Mayo (2012) reported a significant relationship between neighbourhood deprivation and teachers' turnover.…”
Section: Attrition and Working Conditionsmentioning
confidence: 87%
See 1 more Smart Citation
“…This could suggest that schools with more socially disadvantaged students are associated with more attrition or turnover, but this is not so clear. Dupriez, Delvaux, and Lothaire (2015), for example, did not find a significant relationship between these two variables, and, although Borman and Dowling (2008) found a significant relationship in their meta-analysis, the effect size was quite small (only a 5% greater possibility of attrition when the majority of students were from a low socioeconomic background). On the other hand, Allen, Burgess, and Mayo (2012) reported a significant relationship between neighbourhood deprivation and teachers' turnover.…”
Section: Attrition and Working Conditionsmentioning
confidence: 87%
“…This echoes several studies that have found that there is more attrition in schools located in urban areas than in those located in rural areas (Borman & Dowling, 2008;Ingersoll, 2001). However, Dupriez et al (2015) found that there was more turnover in rural areas, a result that they explained in terms of the idiosyncrasies of the Belgian context: a decentralised educational environment and low pressure on the students and schools performances, combined with the advantages of living in more populated cities, encouraged teachers to escape from rural areas and to go to the cities. This explanation (i.e., different social and educational contexts) may indeed be the key to understanding the contradictory results found by researchers about the influence that social deprivation and urban-rural areas have on attrition.…”
Section: Attrition and Working Conditionsmentioning
confidence: 99%
“…Burnout is costly, both personally and for the working environment, since it impairs teachers' functioning, resulting in a decline in quality of work and health (e.g., Saleh and Shapiro 2008;Dupriez et al 2016;Klusmann et al 2008). Teachers who suffer from burnout are more likely to experience the symptoms of depression and sleep disturbances (Saleh and Shapiro 2008;Shin et al 2013), undergo job turnover, and retire earlier (Dupriez et al 2016;Goddard and Goddard 2006). They also provide a lower quality of instruction (Klusmann et al 2008) than their counterparts, who have not experienced burnout.…”
Section: Introductionmentioning
confidence: 99%
“…Effective teachers are considered the key to student learning, so it behooves policymakers, school administration, and society to understand what enhances job satisfaction for teachers which will enhance teacher performance [10]. Researchers such as Darling-Hammond [15], Ingersoll [22,23], Ingersoll and Smith [25], and Dupriez, Delvaux, and Lothaire [16] have shown that if the key elements are identified that are essential to the job satisfaction of teachers, professionals stand to gain a great deal in strengthening the profession.…”
Section: Importance Of Job Satisfactionmentioning
confidence: 99%
“…Thus, administrators and educators alike are concerned about the increased external demands placed on them with little support; moreover, politicians and the media often incriminate teachers for shortcomings of education [11,40,50]. These current conditions have contributed to alarming numbers of teachers leaving the profession of education [16,29]. However, concurrently, there are also teachers so committed to education that they have stayed in teaching despite the obstacles and difficulties [15,31,33].…”
Section: Introductionmentioning
confidence: 99%